The Administration Of Mixture Vibrio Parahaemolytieus And Vibrio Alginolyticus Bacterin and Their Components to Enhance the Survival - Hari Suprapto (Jurnal Sain Veteriner, 2005)
The vibriosis in hatchery and farm easily recognized by the luminous the bacteria present in the water and shrimp itself. The Vibrio sp. used in this experiment were isolated from shrimp and rearing water and the LD50 of V.parahaemolyticus is 10 2'6 and V alginolyticus is 102.5 CFU/fish. The best results obtained from 10 mg/ml mixed of both V.parahaemolyticus and V alginolyticus. The protection of OMP vaccinated fishes was relatively low, the reason could be the OMP contained the low antigenic substance. The SR of fish vaccinated FKC and ICC is 65-70 percent 70-75 percent. Even though it was not proved that FKC and ICC contents more antigenic substance, the FKC and ICC have the higher protein than OMP in measurement of protein and electrophoresis.